Varicella-Zoster virus: A narrative review - Fabian-Alfaro, Angel Carlos (2024)
A review of the various aspects surrounding the varicella-zoster virus is conducted, addressing its morphology, epidemiology, and etiopathogenic mechanisms underlying the disease. Likewise, the different clinical presentations are analyzed, such as varicella, which constitutes the primary infection, and herpes zoster, resulting from virus reactivation. Finally, diagnostic methods, as well as preventive and therapeutic measures, are detailed.